Management of tumor rupture and abdominal compartment syndrome in an infant with bilateral high risk stage 4 neuroblastoma: A case report. Issue 34 (August 2019) - Lode, Holger N.; Henze, Günter; Siebert, Nikolai; Ehlert, Karoline; Barthlen, Winfried
Abstract: Rationale: Tumor rupture and bleeding at initial presentation of infants with neuroblastoma (NBL) is a rare, but life threatening condition and challenge in pediatric oncology. Here, we report successful multidisciplinary management of an abdominal compartment syndrome as a result of tumor rupture and bleeding in an infant with bilateral high risk stage 4 NBL. Patient concerns: The patient was admitted to a cooperating hospital with vomiting, failure to thrive and a large mass in the abdomen and was then referred to our center. Diagnoses: Stage 4 NBL with MYC-N amplification and 1p36 deletion was diagnosed in an 11 months old girl. Due to rapid and massive tumor growth she developed abdominal compression with renal failure, severe bleeding, and tumor lysis syndrome (TLS). Interventions: Surgical decompression by enterostomy, local, and systemic bleeding control with platelets and coagulation factors, antiinfective and TLS therapy were effective in stabilizing the patient's condition. This allowed initiation of the multimodal antineoplastic treatment according to protocol NB 2004. Outcomes: Mechanical ventilation was stopped after 11 days, the abdominal wall was closed 3 months after the start of therapy, and treatment according to the protocol be started and successfully completed. Lessons: Only the immediate, coordinated multidisciplinary intervention managed to overcome the life-threatening abdominal compartment syndrome and its associated problems, eventually enabling successful curative treatment.